Proper Communication Styles in Educational Setting from Lecturers Perspectives - Sdeeq, Balen M. Muhammed; Sulaiman, Evie Farida; Hamad, Chnar Zrar; Abdullah, Zhwan Dalshad (International Journal for Educational and Vocational Studies, 2021)
This study aims to find out the underlying factors of proper communication styles in educational settings from lecturers perspectives. It also tries to find out if there is any significant difference between male and female lecturers perspectives towards proper communication styles, and attempts to determine if there are differences between the private and public universities. Analyzing the data from self-developed questionnaire, yielded four factors; namely (listening, oral, writing, and body language) were derived from the varimax rotated matrix. The results revealed a statistically significant difference between the private and public universities lecturers perspectives towards proper communication. While, no statistically significant difference was found between male and female lecturers in their perspective towards listening, oral, and writing proper communication. The only difference found was in body language communication and it was in favor of female lecturers. The findings of this study will contribute in understanding factors of proper communication styles in educational setting.